THE PUBLIC POLITICS OF SPORTS AND LEISURE AND THE INDEX-FINGER OF SOCIAL CONTROL (Fiep Bulletin - online, 2014)
We used intentional sample and Documentary Research for data collection, regarding the set of proposals proceeding from the states, which had subsidized in the scope of 3 AXLE - Management and Social Control the II National Conference of Sports/2006. We presented the results of the State Conferences, as well as of the Resolution of II the National Conference of the Sport, approved in the final plenary of the respective Conference. Finally is presented a set of pointers to subsidize the social control.
Keywords: Sportive Management; Public Politics; Social Control